Campur Kode Bahasa pada Proses Pembelajaran di PDF Al Huda Malikussaleh - Maulizar Muna; Juni Ahyar; Trisfayani Trisfayani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the form of code mixing in the learning process at PDF Al Huda Malikussleh. The approach used in this study is a qualitative approach with a descriptive research type. The data of this study are interactions, speech and learning materials delivered by teachers at PDF Al Huda Malikussaleh. The source of this data is the teacher of PDF Al Huda Malikussaleh. The data collection technique used in this study is the listening technique without speaking, recording technique and note-taking technique. Based on the results of the study, it was found that 49 code-mixed data. The data were obtained from three different classes with details; 1) class VII Wustha Putra found 13 code-mixed data, 2) class X Wustha Putri found 6 data, and 3) class Ulya found 30 code-mixed data. Furthermore, the code-mixed data are divided into several forms, namely 34 word-form code-mixed data, 8 phrase-form code-mixed data and 7 clause code-mixed data.